Mathematics Learning Difficulties among Elementary School Students - Fitri Yabashiru; Berta Apriza; Karsoni Berta Dinata (Journal for Lesson and Learning Studies, 2025)
Mathematics learning difficulties remain a significant challenge faced by many elementary school students. This issue directly impacts students' low academic achievement in mathematics. This study aims to identify and analyze in depth the various factors causing mathematics learning difficulties using a Systematic Literature Review (SLR) approach. A total of 10 relevant scientific articles were carefully selected based on specific inclusion criteria and analyzed using a thematic approach. The results of this study indicate that there are two main categories of causes of learning difficulties: internal and external factors. Internal factors include a lack of understanding of basic mathematical concepts, low motivation to learn, and excessive anxiety toward mathematics lessons. On the other hand, external factors involve the use of less varied teaching methods, limited learning media, and a lack of support from the surrounding environment, especially from parents. Based on these findings, it is concluded that it is important to apply a contextual, interactive, and student-centered learning approach tailored to students' characteristics and needs. Additionally, strong collaboration between teachers, parents, and school authorities is needed to create a conducive learning environment. The implications of this research indicate that interventions based on students' needs and teacher training in designing more effective learning strategies are essential to address the challenges in mathematics learning comprehensively.